Real-time imaging of myoblast transplantation using the human sodium iodide symporter - Bouchentouf, Manaf (BioTechniques, 2005)
The quantification of the graft success is a key element to evaluate the efficiency of cellular therapies for several pathologies such as Duchenne muscular dystrophy. This study describes an approach to evaluate the success of myoblast transplantation (i.e., survival of the transplanted cells and the muscle fibers formed) by real-time imaging. C2C12 myoblasts were first transfected with a plasmid containing the human sodium iodide symporter (hNIS) gene. Specific uptake of the radioactive sodium pertechnetate (Na99mTcO4) by the hNIS-positive myoblasts was demonstrated in vitro, while only background level of Na99mTcO4 was observed within the control cells. The cells were then transplanted into the tibialis anterior (TA) muscle of mdx (X-linked dystrophic) mice. Following intraperitoneal administration of Na99mTcO4, scintigraphies were performed to detect hNIS-dependent Na99mTcO4 uptake within the TA. This approach permitted to evaluate the progression of the transplantation and the graft success without having to biopsy the animals during the follow-up period